Unsteady convective flow of a preheated water-in-oil emulsion droplet impinging on a heated wall; Physics of Fluids; Vol. 34, iss. 9 - Piskunov M. V. Maksim Vladimirovich; Khomutov N. A. Nikita Andreevich; Semyonova A. E. Aleksandra Evgenjevna; Ashikhmin A. E. Alexander Evgenjevich; Misyura S. Ya. Sergey Yakovlevich (2022, 2022)
Title screen